Synthesis, structure–activity relationship, and mechanistic investigation of lithocholic acid amphiphiles for colon cancer therapy. Issue 1 (29th October 2014) - Singh, Manish; Bansal, Sandhya; Kundu, Somanath; Bhargava, Priyanshu; Singh, Ashima; Motiani, Rajender K.; Shyam, Radhey; Sreekanth, Vedagopuram; Sengupta, Sagar; Bajaj, Avinash
Abstract : We report the enhanced anticancer activities of lithocholic acid amphiphiles possessing different charged head group for colon cancer therapy. Abstract : We report a structure–activity relationship of lithocholic acid amphiphiles for their anticancer activities against colon cancer. We synthesized ten cationic amphiphiles, differing in nature of their cationic charged head groups, using lithocholic acid. We observed that anticancer activities of these amphiphiles against colon cancer cell lines are contingent on nature of the charged head group. The lithocholic acid-based amphiphile possessing a piperidine head group (LCA-PIP1 ) is ∼10 times more cytotoxic than its precursor. Biochemical studies revealed that enhanced activity ofLCA-PIP1 compared to lithocholic acid is due to a greater activation of apoptosis.LCA-PIP1 induces sub G0 arrest and causes cleavage of caspases. A single dose of lithocholic acid–piperidine (LCA-PIP1 ) derivative is enough to reduce the tumor burden by 75% in a tumor xenograft model.